Analisis Keadaan Sosial Tukang Becak Dalam Menghadapi Modernitas Di Stasiun Jember - Diva Ummul Nabilla; Rosita Setyaningrum; Isti Kharimah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Modernity has brought quite significant changes and impacts, especially on social and economic changes. Pedicab drivers are one of the units in society that is experiencing a major impact from the modernization process, they are threatened with losing their jobs, causing the problem of not being able to meet their daily needs. This research aims to provide insight regarding the analysis of pedicab drivers in facing modernity, so that they are expected to have good knowledge regarding the social and economic changes that occur in the community of pedicab drivers at Jember stasion. This research uses qualitative research methods through a phenomenological approach. The basic theory used in this research is the functional structural theory proposed by Talcott Parson. Data collection in this research used interviews, observation, and documentation.